Pendampingan Pembuatan Video Game untuk SMAN 3 Batusangkar - Aina Hubby Aziira; Ricky Akbar; Adi Arga Arifnur; Afriyanti Dwi Kartika; Dwi Welly Sukma Nirad; Febby Apri Wenando; Ullya Mega Wahyuni (Warta Pengabdian Andalas, 2023)
Student creativity in the field of research can develop a method that has excellent potential to be utilized by the wider community. SMAN 3 Batusangkar students have high creativity and interest in participating in research olympiads, such as designing a video game structure as a therapeutic tool to help children with Attention Deficit Hyperactivity Disorder (ADHD) in problems with hyperactivity, impulsivity, and inattention. The designed video game is part of their research plan proposed in the Indonesian Student Research Olympiad. However, the lack of understanding of the students in making video games with the concept of visual attention for children with ADHD to be used in research is a problem in itself. Therefore, the community service team in the Information Systems Department, Universitas Andalas, assisted in making video games to increase the understanding of the SMAN 3 Batusangkar team on making video games. This activity aimed to disseminate process knowledge related to making simple video games to support innovations that benefit society. Assistance was carried out intensively at the Basic Laboratory of the Information Systems Department to help the SMAN 3 Batusangkar team complete a series of research plans proposed for the Olympics, especially at stages related to making video games.